A unit pipe pneumatic model to simulate gas kinetics during measurements of embolism in excised angiosperm xylem. (1st September 2022) - Yang, Dongmei; Pereira, Luciano; Peng, Guoquan; Ribeiro, Rafael V; Kaack, Lucian; Jansen, Steven; Tyree, Melvin T
Abstract: The pneumatic method has been introduced to quantify embolism resistance in plant xylem of various organs by applying a partial vacuum to cut-open xylem. Despite the similarity in vulnerability curves between the pneumatic and other methods, a modeling approach is needed to investigate if changes in xylem embolism during dehydration can be accurately quantified based on gas diffusion kinetics. Therefore, a unit pipe pneumatic (UPPn) model was developed to estimate gas extraction from intact conduits, which were axially interconnected by inter-conduit pit membranes to cut-open conduits. The physical laws used included Fick's law for diffusion, Henry's law for gas concentration partitioning between liquid and gas phases at equilibrium and the ideal gas law. The UPPn model showed that 91% of the extracted gas came from the first five series of embolized, intact conduits and only 9% from the aqueous phase after 15 s of simulation. Considering alternative gas sources, embolism resistance measured with a pneumatron device was systematically overestimated by 2–17%, which corresponded to a typical measuring error of 0.11 MPa for P 50 (the water potential equivalent to 50% of the maximum amount of gas extracted). It is concluded that pneumatic vulnerability curves directly measure embolism of intact conduits due to the fast movement of gas across interconduit pit membranes, while gas extraction from sap and diffusion across hydrated cell walls is about 100 times slower. We expect that the UPPn model will also contribute to the understanding of embolism propagation based on temporal gas dynamics.